Dynamic Behavior of Soft Subgrade Soils Treated with Boron Waste - Volkan Okur; Kubra Akinci (Advances in Materials Science and Engineering)
A series of laboratory tests using resonant column and dynamic torsional shear tests were conducted on kaolinite and montmorillonite clays treated with boron waste. The effect of the boron waste on the dynamic characteristics of two clays was studied considering the effects of the plasticity index. Pulverized boron waste was mixed with the clay soils in different proportions. It has been seen that treatment with boron waste improved the dynamic properties of the two clays. However, increasing the amount of boron waste does not affect the dynamic characteristics of the samples in the same proportions. Increasing the amount of boron waste in the mixture increased the initial shear modulus of the montmorillonite clay up to 300% compared to untreated samples, whereas the reaction of the kaolinite clay with boron waste treatment was moderate. Degradation curves of treated and untreated soils in regard to shear strain are presented. In general treatment, success is dependent on the amount of boron waste and the clay type. The continuous increase with the amount of boron waste in the shear modulus and damping ratio is apparent on both clays.